2017
DOI: 10.1007/s11420-017-9568-2
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions and Current Trends in Internet Use by Orthopedic Outpatients

Abstract: A large proportion of patients use the internet to research orthopedic information and most patients, especially younger males, find the information useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…The Internet is one of the main sources of information that enables users to have access to a larger volume of information in many sectors, regardless of geographic location. Surveys have indicated that most Internet users in the world have used the Internet to get health information 13. Developments in Internet access and improvements in performance due to new technologies have made the Internet the focus of many new health-care improvements 3–7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Internet is one of the main sources of information that enables users to have access to a larger volume of information in many sectors, regardless of geographic location. Surveys have indicated that most Internet users in the world have used the Internet to get health information 13. Developments in Internet access and improvements in performance due to new technologies have made the Internet the focus of many new health-care improvements 3–7.…”
Section: Introductionmentioning
confidence: 99%
“…Surveys have indicated that most Internet users in the world have used the Internet to get health information 13. Developments in Internet access and improvements in performance due to new technologies have made the Internet the focus of many new health-care improvements 3–7. As a result, the Internet is having a significant impact on health and health care, as it has the potential to advance the health-care delivery and support the decision-making of health-care providers 8.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, commercial interests can direct the order of exposure of the websites presented (35) . In some cases, as a result of the terms used in the search, results lead users to consult paid platforms such as commercial websites (36)(37) .…”
Section: Discussionmentioning
confidence: 99%
“…Search engines such as Google and Yahoo account for an estimated 30% of global web traffic [ 4 ] and are commonly used for information prior to seeing a physician or following an appointment. Burrus et al [ 5 ] found that a group of 1,296 patients surveyed at an orthopedic clinic were more likely to research their orthopedic problems on the internet than on the websites of the treating institutions. While adequate preoperative education promotes informed decision-making [ 6 - 10 ], internet utilization as a primary resource for healthcare information presents two major problems: accuracy of information and patient comprehension.…”
Section: Introductionmentioning
confidence: 99%